Analysis of measurement systems mathematical models by using the comparison of functions - Ilkiv V. S.; Nytrebych Z. M.; Pukach P. Ya.; Kohut I. V.; Pakholok B. B.; Iлькiв В. С.; Нитребич З. М.; Пукач П. Я.; Когут I. В.; Пахолок Б. Б. (Lviv Politechnic Publishing House, 2019)
We propose an approach to mathematical modeling for a system on the basis of comparing scalar products in spaces of real functions integrable on the segment. This approach may be used in discrete and continuous measurement systems and some combinatorial systems, in which comparison problem of function exists in the process of synthesis and optimal choice of their parameters. In theory, such problems are characteristic of boundary value problems for equations of mathematical physics, in particular for multi-point problems that describe oscillatory processes in mechanisms. We have found the necessary and sufficientconditions for such a comparison. We use special transformations of sums and integralsthat appear in the corresponding scalar products for vectors and functions. У роботi запропоновано пiдхiд до математичного моделювання систем на основi порiвняння скалярних добуткiв у просторах, iнтегровних на вiдрiзку дiйсних функцiй. Цей пiдхiд можна використовувати у дискретних i неперервних системах вимiрювання та деяких комбiнаторних системах у процесi синтезу та оптимального вибору їх параметрiв, де постає задача порiвняння функцiй. Теоретично такi задачi характернi також для крайових задач для рiвнянь математичної фiзики, зокрема для багатоточкових задач, якi описують коливнi процеси у механiзмах. Знайдено необхiднi й достатнi умови такого порiвняння. Використано спецiальнi перетворення сум та iнтегралiв, якi входять у вiдповiднi скалярнi добутки для векторiв та функцiй.
Аналiз математичних моделей вимiрювальних систем з використанням порiвняння функцiй
Keywords: measurement systems, optimization, scalar product, integration by parts, integrable functions, polynomials, системи вимiрювання, оптимiзацiя, скалярний добуток, iнтегрування частинами, iнтегровнi функцiї, многочлени.